THE INTER-AMERICAN HUMAN RIGHTS SYSTEM AND THE ROLE AND RIGHTS OF JUDGES - Abi-Mershed, Elizabeth (REVISTA ESMAT, 2021)
Access to justice at the domestic level is a core component of human rights protection, with judges playing a key role in that process. Judges may require particular protection when subject to violations of their own rights in connection with their judicial mandate. This article first provides a basic overview of the Inter-American Commission’s and Court’s respective mandates. There are some brief references to examples from Brazil, as well as some concerning judicial independence and the protection of judges. The article then reviews a series of individual cases in which the Commission and Court have set standards on the obligation of states to respect the role and independence of judges. The focus is on independence, through respect for their security of tenure against improper interference, as well as effective protection when judges are subjected to threats or violence due to their work. In relation to judicial protection and guarantees, the article also looks briefly at the system’s clear position against the use of military jurisdiction to investigate, prosecute and punish serious human rights violations. The article closes with a brief reflection on the system and the commonalities and distinctions within which it necessarily works.